5-6x=3(1-2x)

Simple and best practice solution for 5-6x=3(1-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-6x=3(1-2x) equation:


Simplifying
5 + -6x = 3(1 + -2x)
5 + -6x = (1 * 3 + -2x * 3)
5 + -6x = (3 + -6x)

Add '6x' to each side of the equation.
5 + -6x + 6x = 3 + -6x + 6x

Combine like terms: -6x + 6x = 0
5 + 0 = 3 + -6x + 6x
5 = 3 + -6x + 6x

Combine like terms: -6x + 6x = 0
5 = 3 + 0
5 = 3

Solving
5 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3n+6=87 | | Z^2-20z-21=0 | | 5y=3(y-2) | | -21=-5v+3(v-5) | | 3b+16=40 | | -16-9-4x=-9 | | =1+1 | | 8x+20=2x+20 | | -5=6n | | 5-3x+2=4x+7 | | 4x^2-23x+13=-7x+6 | | 24-6m=0 | | .5(10z+8)-2=4(z-6) | | 8+9x=-6 | | 2(x+3)=5+2x | | x/3+4=x/6+2 | | 5x+35=7(x+5)-2x | | 6x+3(1+3x)=3+15x | | 3x^6+192=0 | | 2x+24=4(x+6)-2x | | -9-6k+9-(-2k)= | | (2x+4)+(2x+-9)+x=180 | | (w-5)(w-5)=2w^2-6w+28 | | 8+12k-8k-5k= | | x^2-4x-44=3x-6 | | x^2-7x-38=0 | | 8x+34= | | 5y-4=2y+23 | | 9ln(7x)=72 | | 3(-2)=-9y+33 | | 10k+7-3k-11= | | 5x-8y-15=0 |

Equations solver categories